Case study: Isokinetic rehabilitation of a ruptured biceps tendon - Martens, D.W.; Axtell, R.S.; Stofan, J.R. (Journal of Strength and Conditioning Research, 1995)
A 37-year-old male ruptured the distal biceps brachii tendon performing a gymnastics routine. At Week 8 postsurgery, a bilateral isokinetic test demonstrated a 64 and 50% (at 60° • s-1and 300° • s-1) peak torque deficit between uninjured and injured arms during elbow flexion. The subject participated in a concentric isokinetic exercise program 3 days a week for 4 months. At 1 year postsurgery a bilateral test demonstrated a 14% deficit in peak torque at 60° • s-1, and faster test velocities of 180° • s-1and 300° • s-1indicated higher torques for the injured biceps muscle. The rehabilitation program returned the ruptured biceps to a level of concentric strength nearly equivalent to the contralateral limb at the velocities tested. © 1995 National Strength & Conditioning Association.
Keywords: Avulsion; Bilateral; Specificity; Strength; dept.hms